AESTHETIC RESISTANCE ANALYSIS IN THE KERATON YOGYAKARTA BUILDING COLUMN - Darini Yusrina Abidah; Faiz Ramadiansyah; Sovie Nurmalia Junita; Dian Kartika Santoso (Border: Jurnal Arsitektur, 2024)
Two fundamental requirements for sustainable rural area development are enhancing the well-being of the rural populace and safeguarding cultural assets. The preservation of architectural buildings' aesthetic value is one aspect of cultural preservation, but frequently, welfare improvements do not align with these efforts. It is necessary to draw aesthetic guidelines from construction projects with notable cultural significance. The buildings of Keraton Yogyakarta is a national landmark which has unique aesthetic qualities. The study in question focuses on the building's column in Keraton Yogyakarta and its ability to withstand aesthetic criticism. There are two goals to this architectural research on aesthetic resilience. 1) To determine the aesthetic columns' resilience value in Keraton Yogyakarta buildings; 2) To differentiate architectural parts according to their resilience value. The constructivism research paradigm served as the foundation for the conduct of this research. A combination of qualitative and historical research methods is the research strategy being used in this research. Historical research is used to gather historical data. Qualitative study focuses on the formal nature of an aesthetic to determine its aesthetic resilience value. According to the findings, there are three levels of aesthetic resilience in the decorative components implemented on the columns. 1) the most significant aesthetic resilience is seen in the Javanese ornaments that are still in place; 2) the color of the columns varies over time but still exhibits aesthetic resilience; and 3) there is no aesthetic resilience found in the European features.